Green Synthesis Gold Nanoparticles using Bioreductant Red Shoot Leaf Extract (Syzygium myrtifolium Walp.) and Activity as Antioxidant - Farihah, Neni Isna; Taufikurohmah, Titik (Jurnal Pijar Mipa, 2024)
Gold nanoparticles (AuNPs) are small-sized materials important in various commercial and industrial applications. Several methods have been developed to synthesise AuNPs. This study was conducted by synthesizing AuNPs using HAuCl4 as a precursor and red shoot leaf extract as a bioreductor. The concentrations of AuNPs used were 20, 10, 5, and 2.5 ppm. Characterization of gold nanoparticles at a concentration of 20 ppm was carried out using a UV-Vis spectrophotometer to measure the maximum wavelength and Transmission Electron Microscopy (TEM) to determine particle size. Antioxidant activity at 20, 10, 5, and 2.5 ppm was determined by measuring free radical capture activity using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The results showed that gold nanoparticles had a maximum wavelength of 530 nm with a ruby red color and an average particle size of 14.907 nm. The synthesized AuNPs showed high antioxidant activity: 99.6% (20 ppm), 98.9% (10 ppm), 96.7% (5 ppm), and 91.0% (2.5 ppm), indicating that higher concentrations of AuNPs resulted in more significant free radical scavenging. This study successfully synthesized gold nanoparticles using red shoot leaf extract as an environmentally friendly bioreduction. The resulting nanoparticles have a nanometer particle size with very high antioxidant activity, especially at a concentration of 20 ppm. The method used in this study offers a more environmentally friendly alternative for synthesizing gold nanoparticles, which previously often used hazardous chemicals. The use of red shoot leaf extract as a bioreductor has not been widely reported in the literature, thus providing a new contribution to green nanotechnology. Further research is recommended to explore the potential applications of gold nanoparticles synthesized by this method in medical and other industrial fields. In addition, additional studies are needed to optimize the synthesis conditions and more in-depth characterization of the stability and toxicity of gold nanoparticles in practical applications.